2x + 2(5+x)=10
2x+10+2x=10
4x+10=10
4x=0
X=0
Answer:
Solution (7,1)
Step-by-step explanation:
Use the elimination method
x + y=8
x - y=6
--------------Add
2x = 14
x = 7
Substitute x = 7 into x + y=8
7 + y=8
y = 8 - 7
y = 1
Solution (7,1)
Answer:
y^3/(27 x^3)
Step-by-step explanation:
Simplify the following:
((3 x)/y)^(-3)
((3 x)/y)^(-3) = (y/(3 x))^3:
(y/(3 x))^3
Multiply each exponent in y/(3 x) by 3:
(y^3)/((3 x)^3)
Multiply each exponent in 3 x by 3:
y^3/(3^3 x^3)
3^3 = 3×3^2:
y^3/(3×3^2 x^3)
3^2 = 9:
y^3/(3×9 x^3)
3×9 = 27:
Answer: y^3/(27 x^3)
Answer:
y=45
x=9
z= 9 root 2
Step-by-step explanation:
This is a right isosceles triangle, so
y=45
x=9
z= 9 root 2
9²+9²=z²
81+81=z²
162=z²
√162=z
z=9√2